Stock prices, uncertainty and risks: Evidence from developing and advanced economies - Mary Elena Sánchez-Gabarre (European Journal of Government and Economics (EJGE), 2020)
This paper studies the relationship between stock prices and three types of uncertainty: economic policy uncertainty, stock market volatility, and geopolitical risks. In particular, our aim is to determine whether these forms of uncertainty play the same role in developed and developing countries. With this purpose, we take Spain and Brazil as representative cases. In order to provide new insights into the abovementioned relationship, a cointegration approach is applied, specifically an ARDL model, using monthly data from the period January 2006-December 2019 for a series of financial and macroeconomic variables. The results obtained reveal that there is no uniform effect of uncertainty in stock markets of developing and developed countries. First, in Spain, there is a high perception of uncertainty in economic policy and stock market volatility, which impact negatively in share prices, both in the short and long term. Regarding Brazil, the global uncertainty in the stock markets has effects on share prices, in both time horizons. By contrast, geopolitical risks do not show any significant impact on Brazilian and Spanish share returns.
Keywords: C22; G12; G18; 330; economic policy uncertainty; geopolitics; stock markets; uncertainty; volatility